(9b-7)-4(2b+1)=-3

Simple and best practice solution for (9b-7)-4(2b+1)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9b-7)-4(2b+1)=-3 equation:


Simplifying
(9b + -7) + -4(2b + 1) = -3

Reorder the terms:
(-7 + 9b) + -4(2b + 1) = -3

Remove parenthesis around (-7 + 9b)
-7 + 9b + -4(2b + 1) = -3

Reorder the terms:
-7 + 9b + -4(1 + 2b) = -3
-7 + 9b + (1 * -4 + 2b * -4) = -3
-7 + 9b + (-4 + -8b) = -3

Reorder the terms:
-7 + -4 + 9b + -8b = -3

Combine like terms: -7 + -4 = -11
-11 + 9b + -8b = -3

Combine like terms: 9b + -8b = 1b
-11 + 1b = -3

Solving
-11 + 1b = -3

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1b = -3 + 11

Combine like terms: -11 + 11 = 0
0 + 1b = -3 + 11
1b = -3 + 11

Combine like terms: -3 + 11 = 8
1b = 8

Divide each side by '1'.
b = 8

Simplifying
b = 8

See similar equations:

| (3x-4)+10=5(x+4) | | 63x^3-28x^2+45x-20=0 | | 3+23a= | | 27x^3-18x^2+9x=0 | | 9w^2+21w-8=0 | | -9(x-27)+3(x+3)=x-17 | | -21x^7-7x^6=0 | | -16x=-4x^3 | | -4(5n+6)=8 | | -(7y+2)-(-6y-6)=-1 | | 8(3x-1)=4(6x+3) | | 8+8y-3=8y+20-5y | | (4a*2)+2+(5a*3)+1= | | log*5*(x-3)=3 | | 16r+9r=225 | | 5a-7b+2b=0 | | (4a)(2+2)+(5a)(3+1)= | | (-3p)4= | | -7.2x=57.6 | | ln*(12x-6)=ln*12 | | x^2-28x+80=0 | | -4(3b+3)+(13b-6)=0 | | 7X+5x=5x+17 | | 3.7q-5.1-4.5q=-1.8q-1.5 | | 3n-9=7n+5 | | x^2=-15x-54 | | X^2-9=49 | | 3x^2+24x=-49 | | 5x^2+6x=33x-10 | | (x-1)(3x-4)=2 | | x(5x-9)=18 | | -(7y+2)-(-6y-5)=-5 |

Equations solver categories